Design of a randomised, double-blind, crossover, placebo-controlled trial of effects of sildenafil on cerebrovascular function in small vessel disease: Oxford haemodynamic adaptation to reduce pulsatility trial (OxHARP). (September 2021) - Webb, Alastair; Werring, David; Dawson, Jesse; Rothman, Alex; Lawson, Amy; Wartolowska, Karolina
Background: Cerebral small vessel disease (SVD) is associated with increased cerebrovascular pulsatility, endothelial dysfunction, and impaired vascular reactivity. Vasodilating phosphodiesterase inhibitors may improve cardiovascular pulsatility and reactivity, and potentially reduce progression of SVD. Hypothesis: Sildenafil, a PDE5 inhibitor, will reduce cerebrovascular pulsatility and increase cerebrovascular reactivity compared to placebo, and is non-inferior to cilostazol, a PDE3 inhibitor. Methods: OxHARP is a randomised, double-blind, crossover trial of sildenafil 50 mg thrice daily, cilostazol 100 mg twice daily and placebo in 75 patients with mild to moderate small vessel disease and a previous lacunar or cryptogenic stroke or TIA. Participants undergo a physiological assessment at baseline and on each treatment, including transcranial Doppler ultrasound (TCD, DWL DopplerBox) to assess cerebrovascular pulsatility and reactivity to 4–6% carbon dioxide. In up to 60 patients, cerebrovascular pulsatility, perfusion and reactivity will also be assessed by MRI. Outcome measures: The primary outcome is difference in middle cerebral artery pulsatility (Gosling's Pulsatility Index, PI) after 3 weeks of sildenafil versus placebo. Secondary outcomes including non-inferiority of sildenafil vs cilostazol in effects on PI, percentage increase in MCA blood flow velocity and BOLD-fMRI response during inhalation of 4–6% carbon dioxide. Discussion: Reduction in cerebral pulsatility and increased cerebrovascular reactivity during treatment with sildenafil would indicate potential benefit to prevent progression of SVD, suggesting a need for trials with clinical outcomes. Trial Registration OxHARP is registered with ClinicalTrials.org, NCT03855332